The trend in short selling and the cross section of stock returns - ZHU, Zhaobo (Institutional Knowledge at Singapore Management University, 2019)
This paper documents that stocks with a decreasing (increasing) trend in their short selling as proxied by the long-term change in short interest experience significant and positive (negative) abnormal returns. Moreover, the positive abnormal returns have larger absolute values and are more persistent. The return predictability of the trend in short selling is not subsumed by the level of short interest and other well-known determinants of stock returns. Investor sentiment does not affect the profitability of the trend strategy. Our results suggest that market participants underreact to public information on short interest and that short sellers are sophisticated investors.